Struggle and Class Conflict: an Analysis of Social Domination in Red Rising by Pierce Brown : Perjuangan dan Konflik Kelas: Analisis Dominasi Sosial dalam Red Rising oleh Pierce Brown - Afandik, Mochammad Aril; Supsiadji, Mateus Rudi; Supsiadji, Mateus Rudi (Proceeding of Conference on Literature, Linguistic, and Cultural Studies, 2025)
This study analyzes the representation of social domination and class conflict in Pierce Brown’s science fiction novel Red Rising. Building on the perspective that literary works reflect and critique social realities, the main focus of this study is on the social class structure, exploitation, and dynamics of resistance depicted in the narrative. The research aims to examine the color-based caste system that shapes the societal hierarchy in the novel and how class conflict and resistance against this system are manifested through the journey of the main character, Darrow. Utilizing Karl Marx’s Marxist theory as a theoretical framework, this study explores key concepts such as social class, ideology as a tool of domination, class conflict, and alienation. A descriptive qualitative approach, combined with intrinsic (structuralist) analysis and Marxist literary criticism, is employed to analyze data from the novel’s narrative, dialogues, and setting descriptions. The findings indicate that the society in Red Rising exhibits an extreme class division: the Golds as the ruling bourgeoisie controlling all aspects of life, and the Reds as the proletariat living in brutal exploitation and inhumane working conditions. Gold domination is maintained through claims of genetic superiority, ideological manipulation that creates “false consciousness,” and strict military force and information control. Darrow’s journey, initially alienated and influenced by propaganda, drastically changes after the death of his wife, Eo, which ignites his class consciousness. This transformation compels Darrow to infiltrate the Gold system and lead strategic resistance from within, establishing him as a symbol of proletarian revolution demonstrating the potential for radical social change. Keywords: Alienation, Class Conflict, Marxist Theory, Red Rising, Socio-Political.